The middle-aged women's attitudes towards (anti-ageing) cosmetic services in the Czech Republic - Honelová, M; Doseděl, T (Acta chirurgiae plasticae, 2025)
Cosmetic/aesthetic surgery has increased in popularity, reflecting the increased consumer demand. Modern women feel compelled to meet near-impossible standards of beauty. Most of those who undergo cosmetic/aesthetic surgery are (middle-aged) women. Women are often under pressure to meet near-impossible standards of beauty. This study examined cosmetic/aesthetic surgery attitudes and perceptions among 516 Czech middle-aged women. It assessed the perception and attitudes towards cosmetic/aesthetic procedures of middle-aged Czech women and determined the possible factors influencing their level of acceptance through a quantitative survey. The research findings are based on an online questionnaire survey. Based on our analyses, we revealed that acceptance and attitudes towards cosmetic/aesthetic surgery among women can be influenced by the variables such as marital status, place of living, fear of ageing, the importance of physical appearance, occupational status, and partner's influence. This study provided a first general look at the situation around cosmetic/aesthetic surgery in the context of the Czech Republic. However, to gain a more comprehensive understanding of the acceptance and attitudes towards cosmetic/aesthetic surgery in the Czech Republic, further research should be conducted across the country to assess the attitudes of the wider population (for example, different age groups).
Keywords: dospělí; Aesthetic surgery; plastická chirurgie; Humans; cosmetic surgery; attitudes; lidé středního věku; Middle Aged; acceptance; Czech Republic; Surveys and Questionnaires; Česká republika; middle-aged women; Aging; Surgery, Plastic; Adult; průzkumy a dotazníky; ženské pohlaví; lidé; stárnutí; Female